Optimizing Motivation: Leadership Style that Inspires the Work Environment - Dira, Aldi Friyatna; Sawitri, Ina; Abdulrahman, Abdulrahman; Utomo*, Kurniawan Prambudi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
The purpose of the research is to determine the influence of each variable of leadership style and work environment on motivation, as well as to optimize these variables in order to enhance employee motivation. This research method employs quantitative descriptive analysis using SPSS V.26 on the results from 40 respondents. The findings from the employees of the Transportation Department and the community as users of related transportation services indicate that the variables of the work environment’s role and leadership style have a significant positive impact on employee motivation. Therefore, it is recommended that the Transportation Department (Dishub) of Bekasi City should continue to maintain a harmonious relationship between leaders and employees to improve performance, thereby producing effective and adequate transportation services to increase the satisfaction of the Bekasi City community as users of transportation services. Keyword: Optimization; Work Environment; Leadership Style; Motivation; Employees